Environmental risk perception and public trust—from planning to operation for China's high-speed railway. Issue 9 (21st October 2017) - Guo, Dong; He, Guizhen; Lian, Zi
ABSTRACT: China has the world's largest high-speed railway (HSR) network, but while HSR is meeting high transportation demand, the Decide-Announce-Defend approach to infrastructure policy and projects still prevails in China and is often criticized for not addressing public concerns of environmental and social risks. In recent years, researchers have investigated the economic and environmental impacts of HSR, yet few studies have evaluated the public's views on HSR risks or their views on the trustworthiness of key information sources, which are believed to be critical in predicting public behavior and reaction to infrastructure projects. Using random survey data from communities along the Beijing-Shenyang and Beijing-Shanghai high-speed railway lines, our study shows that perceived risks of HSR are higher in the operating stage rather than during construction. We also find that in the construction stage, risk-related information is often obtained through informal channels, while the government becomes a more trusted information provider only after HSR goes into operation. Furthermore, we confirm that the public's perception of the level of knowledge, transparency, and attention to risk of the information sources 1 are key determinants of their perceived trustworthiness. Lastly, this study reveals that socioeconomic characteristics are more important than project phase in explaining the regional differences in risk perception and trustworthiness of key information sources. This key finding calls for a strategy of stakeholder engagement that is carefully tailored to the demographics of the affected population in the decision-making and implementation process of HSR, as well as other infrastructure projects.